Teachers’ Use of Within-Class Ability Groups in the Primary Classroom: A Mixed Methods Study of Social Comparison - Webb-Williams, Jane Louise (Frontiers in Psychology, 2021)
It is common practice within primary classrooms for teachers to spilt children into different ability groups so that children of similar level are taught together. Whilst this practice is used across the globe, research is mixed on the benefits of such grouping strategy. This paper presents data collected from mixed methods research which investigated teachers use of grouping strategies and social comparison, the act of comparing oneself with others. It focuses on when, why and with whom children from different ability groups compare themselves and the impact this has on their self-perceptions. Drawing upon data from children aged between 10 and 11 years from twelve primary schools, social comparison was found to play a significant role in daily classroom life for some children. The study identified different strands of the social comparison process including acknowledgement, topic, target, and direction, and it revealed positive and negative effects of social comparison. A difference by ability group was identified. Children within the low ability group were particularly vulnerable to the negative effects of social comparison and found to engage in more frequent and intentional social comparisons which were heavily relied upon for self-evaluation and performance evaluation. The paper discusses the educational implications of social comparison regarding pupil ability grouping strategies, motivation, engagement, and academic performance. Implications for teacher education and professional development is discussed.